2002
DOI: 10.1161/01.cir.0000028336.95629.b0
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Systolic Unloading and Augmentation of Intracoronary Pressure and Doppler Flow During Enhanced External Counterpulsation

Abstract: Background-Enhanced external counterpulsation (EECP) is a noninvasive, pneumatic technique that provides beneficial effects for patients with chronic, symptomatic angina pectoris. However, the physiological effects of EECP have not been studied directly. We examined intracoronary and left ventricular hemodynamics in the cardiac catheterization laboratory during EECP. Methods and Results-Ten patients referred for diagnostic evaluation underwent left heart catheterization and coronary angiography from the radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
120
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 24 publications
3
120
0
1
Order By: Relevance
“…In our study, patients were on optimal tolerated CAD and HF regime but continue to have severe symptoms with low functional capacity. EECP is a noninvasive, pneumatic technique that utilizes electrocardiogram gated diastolic inflation of a series of lower-extremity cuffs to effectively increase diastolic and mean intracoronary pressures as well as coronary flow while reducing systolic pressure in the central aorta and the coronary artery (18). In addition, EECP improves diastolic filling, decreases left ventricular end-diastolic pressure, and improves LV peak filling rate, end-diastolic volume, and time to peak filling rate (19).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients were on optimal tolerated CAD and HF regime but continue to have severe symptoms with low functional capacity. EECP is a noninvasive, pneumatic technique that utilizes electrocardiogram gated diastolic inflation of a series of lower-extremity cuffs to effectively increase diastolic and mean intracoronary pressures as well as coronary flow while reducing systolic pressure in the central aorta and the coronary artery (18). In addition, EECP improves diastolic filling, decreases left ventricular end-diastolic pressure, and improves LV peak filling rate, end-diastolic volume, and time to peak filling rate (19).…”
Section: Discussionmentioning
confidence: 99%
“…23 On the other hand, several studies have demonstrated increased myocardial perfusion with associated release of endothelial growth factors, improved coronary endothelial function, and decreased neurohumeral factors, which may reflect improved ventricular hemodynamics. 3,[5][6][7] Hence, the bulk of the evidence to date suggests that EECP exerts its sustained clinical benefits through improvements in cardiac status, rather than benefitting the peripheral vascular system. Our study result supports this theory by failing to demonstrate any measurable change in central or peripheral arterial stiffness immediately or 4 months post completion of EECP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…4 The hemodynamic effects are similar to intra-aortic balloon pumping (IABP). 6,7 A treatment procedure involves one to two hours/day for a total of 35 hours of therapy. Several studies around the world have shown patient improvement with lowering in Canadian Cardiovascular Society Classification (CCS) angina class.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, the mechanisms by which these hemodynamic effects lead to a reduction of angina are poorly understood, although the effect is similar to IABP. 7 There is accumulating evidence suggesting that EECP treatment improves endothelial function, which may contribute to the clinical benefit . 8 EECP treatment is associated with an immediate increase in blood flow in multiple vascular beds including the coronary arterial circulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation